2021
DOI: 10.1016/j.biomaterials.2021.120820
|View full text |Cite
|
Sign up to set email alerts
|

Patterned, organoid-based cartilaginous implants exhibit zone specific functionality forming osteochondral-like tissues in vivo

Abstract: Tissue engineered constructs have the potential to respond to the unmet medical need of treating deep osteochondral defects. However, current tissue engineering strategies struggle in the attempt to create patterned constructs with biologically distinct functionality. In this work, a developmentally-inspired modular approach is proposed, whereby distinct cartilaginous organoids are used as living building blocks. First, a hierarchical construct was created, composed of three layers of cartilaginous tissue inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 82 publications
1
51
0
Order By: Relevance
“…It seems that the human iPSC‐derived chondrocytes used in our study have enhanced matrix formation potential compared to GelMA‐embedded primary chondrocytes used in other reports, confirming the higher metabolic performance of these younger iPSC‐derived chondrocytes, which has also been described in pellet culture studies (Castro‐Viñuelas et al, 2018; Loeser, 2009). Our research group has recently compared human iPSC‐derived chondrocytes to adult human articular chondrocytes, showing that iPSC‐derived chondrocytes had increased mRNA expression of the early chondrogenic marker SOX9 and COL2A1 (Hall et al, 2021). An additional possible explanation for enhanced matrix formation in our setup, compared to other GelMA‐based studies, can be found in the origin of the gelatin used for GelMA, as Pahoff et al (2019) recently described that bovine gelatin is preferred over porcine gelatin for the development of hyaline cartilage‐like neotissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that the human iPSC‐derived chondrocytes used in our study have enhanced matrix formation potential compared to GelMA‐embedded primary chondrocytes used in other reports, confirming the higher metabolic performance of these younger iPSC‐derived chondrocytes, which has also been described in pellet culture studies (Castro‐Viñuelas et al, 2018; Loeser, 2009). Our research group has recently compared human iPSC‐derived chondrocytes to adult human articular chondrocytes, showing that iPSC‐derived chondrocytes had increased mRNA expression of the early chondrogenic marker SOX9 and COL2A1 (Hall et al, 2021). An additional possible explanation for enhanced matrix formation in our setup, compared to other GelMA‐based studies, can be found in the origin of the gelatin used for GelMA, as Pahoff et al (2019) recently described that bovine gelatin is preferred over porcine gelatin for the development of hyaline cartilage‐like neotissue.…”
Section: Discussionmentioning
confidence: 99%
“…Human pluripotent stem cells that undergo mesoderm induction exhibit a decrease in pluripotency markers (Nanog, Oct3/4, and Sox2), while primitive streak markers (Brachyury, MIXL1, and KDR) are transiently upregulated. Next, upon chondrogenic differentiation, an increase in SOX9, Col2A1, and ACAN as well as Safranin O and collagen type II positive matrix is observed (Hall et al, 2021; Tam et al, 2021; Yamashita et al, 2015). Authors have shown the in vitro and in vivo cartilage‐producing potential of iPSC‐derived chondrocytes in a scaffold‐free approach, or in combination with hydrogels, such as alginate, chondroitin sulfate PEG, and nanofibrillated cellulose (Ko et al, 2014; J. Lee et al, 2015; Nakamura et al, 2021; Nguyen et al, 2017; Yamashita et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as no tumors were formed after the transplantation in the articular defects, the 3D cultures were concluded to have relatively low tumorigenic risk. In a 2021 study performed by Hall et al, iPSC-derived cartilage organoids generated from the same protocol were implanted into osteochondral defect models [142]. Therefore, the hiPSC-derived scaffold-less cartilage model is expected to increase the clinical application of 3D cultures in treating cartilage conditions.…”
Section: Ipsc-derived Oa-related 3d Model Constructionmentioning
confidence: 99%
“…Third, implanted substitutes that can easily integrate into the host native tissues with immunocompatibility and biocompatibility. During the past decade, we have witnessed advanced progress in the field of cartilage TE, embodied by the following changes: (i) sufficient seed cell selection for applications (mesenchymal stem cells, induced pluripotent stem cells) [ [6] , [7] , [8] ]; (ii) precise patterning of biomaterials and novel biomaterials with advanced chemistries (more efficient and versatile biomaterial conjugations) [ 1 , 9 , 10 ]; (iii) active modulation of cellular biological functions and behaviors via structure and properties (e.g., stiffness, viscoelasticity, porosity and degradability) of biomaterials [ [11] , [12] , [13] ]; (iv) combination of biological drugs and factors are combined to improve bioavailability and bioactivity [ [14] , [15] , [16] ]; (v) rapid development of biofabrication technologies including programmed self-assembly and three-dimensional (3D) bioprinting [ [17] , [18] , [19] , [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%